Chinese fortune stick drawing: supernatural narrative in the The Story of the Stone - Yutong Zheng (Cogent Arts & Humanities)
As a popular religious practice in Chinese folklore, the fortune stick drawing (Qiu Qian 求籤) has become one of the ways to seek good fortune and predict the future. The Shuo Wen Jie Zi (說文解字) states that a fortune stick represents a prophecy from a deity. The appearance of the fortune stick drawing in fiction texts usually has a supernatural and religious dimension because it is able to be fulfilled, and usually requires a connection to a specific deity. Looking back at the history of the fortune stick drawing, it can be seen that as a religious practice, it has been clearly recorded at the end of the Tang Dynasty. By the Song Dynasty, it was widely practiced in temples and Daoist monasteries. As a religious ritual and a supernatural practice, the fortune stick drawing also appeared in Chinese literary works. This paper aims to explore the practice of the fortune stick drawing and prophecy fulfillment in The Story of the Stone(Dream of the Red Chamber 紅樓夢). Previous studies on the novel have rarely focused on the fortune stick drawing. This paper takes a look at the game of ‘Choosing the Flower’ (Zhan Hua Ming 占花名) in Chapter 63 and Wang Xi Feng’s ‘Drawing fortune sticks at Scattered Flowers Convent’(San Hua Si Qiu Qian 散花寺求籤) in Chapter 101, pointing out that although ‘Choosing the Flower’ takes the form of a reunion game, it has a mirror-like structure with the ritual of the fortune stick drawing in different dimensions, and it is also fulfilled in the destiny of the participants. In contrast, ‘Drawing fortune sticks at Scattered Flowers Convent’ is a practice in which the character actively draws a fortune by personal will and with self-consciousness. Furthermore, it is noted that the depictions of the fortune stick drawings and prophecy fulfillments are all related to the supernatural figure of the flower deity (Hua Shen 花神). From the unconscious practice of fortune stick drawing (Choosing the Flower) to the conscious behavior of fortune stick drawing at Scattered Flowers Convent, the novel connects the narrative line from ‘Farewell to flowers’ (Song Hua 送花) to ‘Scattered flowers’ ‘(San Hua 散花)’ centered on the flower deity. Hence, taking The Story of the Stone as an example, this paper tries to analyze the different narrative forms of the supernatural activities such as the fortune stick drawing and prophecy fulfillment of the deities. It also explores how the use of this supernatural activity in the novels reflects the growing trend of folk religions at that time.